Comparison of Antibacterial Effect of Fluoride and Chlorhexidine on Two Cariogenic Bacteria: An in Vitro Study - Poureslami HR; Barkam F; Poureslami P; Salari Z; Salari S (Shiraz University of Medical Sciences, 2014)
Statement of problem: Dental plaque is the main source for dental caries and there is no proper vaccine that can affect dental plaques. Objectives: Daily use of an efficient anti-plaque product can be very beneficial in plaque control and, thus, prevention of caries. This study aims to evaluate the antibacterial effects of four products of Chlorhexidine and Fluoride on two types of cariogenic bacteria. Materials and Methods: In this in vitro study, the antibacterial effect of Chlorhexidine and Fluoride (gel and solution) against Streptococci Sanguis and Sobrinus was evaluated. Chlorhexidine gluconate 1% gel (Corosodyl, France), Chlorhexidine gluconate 2% solution (Consepsis, Ultradent, US), Sodium fluoride 0.2% solution (Oral-B, US) and Acidulated Phosphate Fluoride 1.23% gel ( Denti-Care, Canada) were used. The disc diffusion method was used for testing bacterial sensitivity. The data were analyzed using paired t-test and Chi-square test. Results: In comparison with the negative control, each of the four gels and solutions showed antibacterial effects but the effects were not statistically significant for fluoride solution (P=0.217). For S. Sobrinus, the mean diameter of inhibition zone around the discs coated with fluoride gel (F g), fluoride solution (F s), Chlorhexidine gel (CHX g) and Chlorhexidine solution (CHX s) were 19, 9, 21.5 and 27.5mm, respectively. For S. Sanguis, the mean diameter of inhibition zone around the discs coated with F g, F s, CHX g and CHX s were 17, 11, 17 and 25mm, respectively. CHX s had the most effect on both bacteria and F s had the least. CHX g and F g were less effective than CHX s, respectively. Conclusion: The results demonstrated that 2% CHX s and 1.23% F g can be effective on inhibition of the growth of some of cariogenic bacteria. Therefore, these agents can be used in the prevention of Early Childhood Caries.